Uma análise sócio interacional da relação professor/aluno surdo nas aulas de língua portuguesa numa escola estadual de ensino médio de Campo Grande/RN - Holanda, Joseany Maria Pimenta de (Universidade Federal Rural do Semi-Árido, 2019)
The present research focuses on the socio-interactional relationship between teacher and deaf student. Thus, the aim of this study is to analyze the relationship between the teacher and the deaf student in Portuguese language classes at a secondary school in Campo Grande -RN. We specifically aimed to identify the strategies used by the listener teacher of portuguese language in the interaction with the deaf student during the lessons. To obtain the data, we performed a field diary and an interview with a Portuguese language teacher through a semistructured questionnaire. The research is ofinterpretivequalitative nature, adopting asprocedure the field research, and is based on a previous bibliographic study. For the reasoning, we use authors who discuss the theme, such as: Quadros (2006), Lacerda (2006) and Vigotsky (2007) and others. The research universe involved a public school in the city ofCampo Grande -RN that specifically attends high school, having a total of 378 students, being only a deaf student, in which is the subject of this research. Thus, the corpus is constituted of the answers of the questionnaire about some methodological aspects of learning and more intensely of the interactions teacher listener -deaf student. As results, we verified that the collaboratingteacher has an excellent academic formation, but she did not have any contact with the Brazilian Sign Language in her graduation and recognizes her limitations oninteraction with the deaf student for not knowing Libras, still adds that despite the especial education be part of the brazilian constitution, this right has not been ensured and the state has acted with negligence.
Keywords: Surdo; Interação; Aprendizagem; Libras; LINGUISTICA, LETRAS E ARTES::LETRAS::LETRAS LIBRAS